2019
DOI: 10.1590/1678-7757-2018-0453
|View full text |Cite
|
Sign up to set email alerts
|

Increased whitening efficacy and reduced cytotoxicity are achieved by the chemical activation of a highly concentrated hydrogen peroxide bleaching gel

Abstract: Objective: This study was designed for the chemical activation of a 35% hydrogen peroxide (H 2 O 2) bleaching gel to increase its whitening effectiveness and reduce its toxicity. Methodology: First, the bleaching gel-associated or not with ferrous sulfate (FS), manganese chloride (MC), peroxidase (PR), or catalase (CT)-was applied (3x 15 min) to enamel/dentin discs adapted to artificial pulp chambers. Then, odontoblast-like MDPC-23 cells were exposed for 1 h to the extracts (culture medium + components release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 39 publications
0
40
2
3
Order By: Relevance
“…At the same time, the elimination of these free radicals by the presence of enzymatic and non‐enzymatic antioxidants in the extract limits its deleterious effects on the enamel (Gopinath et al, ; Spychalla & Desborough, ). A recent study showed that the peroxidase may induce the formation of oxidative intermediates through the one‐electron reduction step, called peroxidase cycle (Soares et al, ). This would increase the oxidative potential of hydrogen peroxide, leading to an increase in free radical liberation, also increasing bleaching efficiency and reducing the deleterious effects in the pulp cells (Soares et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, the elimination of these free radicals by the presence of enzymatic and non‐enzymatic antioxidants in the extract limits its deleterious effects on the enamel (Gopinath et al, ; Spychalla & Desborough, ). A recent study showed that the peroxidase may induce the formation of oxidative intermediates through the one‐electron reduction step, called peroxidase cycle (Soares et al, ). This would increase the oxidative potential of hydrogen peroxide, leading to an increase in free radical liberation, also increasing bleaching efficiency and reducing the deleterious effects in the pulp cells (Soares et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the peroxidase may induce the formation of oxidative intermediates through the one‐electron reduction step, called peroxidase cycle (Soares et al, ). This would increase the oxidative potential of hydrogen peroxide, leading to an increase in free radical liberation, also increasing bleaching efficiency and reducing the deleterious effects in the pulp cells (Soares et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,11 With the aim of preventing cellular damage resulting from professional bleaching, and consequently making these therapy safer, various researchers have proposed the addition of catalyst agents to the gels used in-office, based on understanding of the kinetic behavior of H 2 O 2 . [12][13][14] Ortecho-Zuta et al 13 demonstrated that the incorporation of 10 mg/ml of the enzyme Horseradish Peroxidase (HRP) into a bleaching gel with 35%H 2 O 2 limited the trans-amelodentinal cytotoxicity of the product and increased its bleaching efficacy right after the 1st session. The subproducts generated by the decomposition of H 2 O 2 , such as the hydroxyl radical (HO • ), peri-hydroxyl (HO 2…”
mentioning
confidence: 99%